The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0ce01306d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solvent on crystal nucleation of benzocaine

Abstract: The influence of the solvent in nucleation of benzocaine FII was explored by measuring nucleation induction times, probing solvent–solute interactions with spectroscopy and modelling the strength of solvent–solute intermolecular interactions using DFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Finally, we screened the sources of palladium and studied five different palladium catalysts. Therefore, we found that [PdCl (C 3 H 5 )] 2 is the best palladium source (Table 1, entry [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we screened the sources of palladium and studied five different palladium catalysts. Therefore, we found that [PdCl (C 3 H 5 )] 2 is the best palladium source (Table 1, entry [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no infrared peak shift was observed during the whole process, indicating that the solute molecules may exist stably in a certain mode in solution. The −CO stretch mode is a sensitive probe to distinguish aggregation modes due to their differences in hydrogen bond strength. It can be seen from Figure a,b that the stretching vibration peaks of −CO in ethanol and the ethanol/ n -heptane system are both located at 1705 cm –1 , indicating that the chlorpropamide molecules may exist in the form of solvated monomers. Furthermore, it is worth noting that, in ethanol/ n -heptane, apart from the main peak at 1705 cm –1 , the shoulder peak at 1725 cm –1 may represent the presence of weaker interaction solvent–solute clusters.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, there is significant research interest in establishing a relationship between nucleation pathway and solution structure, with the observed nucleation induction time, in order to improve process understanding and control over crystal nucleation from solution. Previous literature has reported that solvent–solute interactions (i.e., the overall solvent–solute interaction or the specific site's solvent–solute interaction) was correlated with the impeded nucleation salicylic acid, 15 isonicotinamide, 21 risperidone, 22 etoricoxib, 23 p ‐nitrobenzoic acid, 24 and benzocaine 25 . In these cases, stronger solute–solvent interaction resulted in higher energy barrier for nucleation resulting in reduced rates of nucleation or extended induction times.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has reported that solvent-solute interactions (i.e., the overall solvent-solute interaction or the specific site's solvent-solute interaction) was correlated with the impeded nucleation salicylic acid, 15 isonicotinamide, 21 risperidone, 22 etoricoxib, 23 p-nitrobenzoic acid, 24 and benzocaine. 25 In these cases, stronger solute-solvent interaction resulted in higher energy barrier for nucleation resulting in reduced rates of nucleation or extended induction times.…”
mentioning
confidence: 99%